Dogoterapia w pracy logopedycznej - Machoś-Nikodem, Marzena (Logopedia Silesiana, 2012)
Pet therapy in the work of a logopedThe article concerns talking the adventage of a therapy with the participation of a dog inthe work of logoped. It presents the terminology connected with the pet therapy. The author describesa therapy model of dyslalia and oligophasia with talking adventage of a dog as a therapeut. In introdusesinto anissve of the pet therapy, which can be a form of the multisensory stimulation to teaching.